Care and Academic Motherhood: Challenges for Research and Tenure in the Canadian University - James, Yvonne; Bourgeault, Ivy; Gaudet, Stephanie; Bujkai, Merridee (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2021)
In Canada, women are earning an increasing number of doctoral degrees; yet, they are less likely to secure a tenure-track position. A feminist thematic analysis of semi-structured interviews with 20 academic mothers from two Canadian universities reveals the range of challenges that mothers encounter in relation to care on the tenure-track. First, the theme of “fear of post-partum academic erasure” captured faculty mothers’ experiences of feeling compelled to assert their physical and intellectual presence in post-partum during peak periods of infant care. The second theme, “the mommy tenure track and care choices,” encapsulated academic mothers’ experiences of feeling unsupported by the university in their pursuit of promotion and tenure given care responsibilities associated with motherhood. The final theme, “research while caring,” captured the tensions academic mothers experience between the research process and caring. The findings of this research are particularly relevant in a pandemic and post-pandemic environment, where academic mothers have seen their care work swell to unprecedented proportions.